POTENSI PENURUNAN DOWNTIME POMPA BRAN LUEBBE DALAM PENGOLAHAN MINYAK KELAPA SAWIT DENGAN METODE RELIABILITY CENTERED MAINTENANCE DI PT X - Hendra Tongam Maraden Purba; Masdania Zurairah; M Fiza Lubis (Jurnal Ilmiah Hospitality, 2023)
Research has been carried out on the components of the diaphragm, check valve, bleed valve and replenishing valve which are components that have the highest damage frequency of 50.64%. Treatment using the Reliability Centered Maintenance (RCM) method shows that all critical component failure modes can be overcome by Condition Directed (CD). Furthermore, with Reliability Centered Maintenance (RCM) as a maintenance method for critical components, a potential reduction of an average downtime of 34.025%.